Effects of coated sodium butyrate on the growth performance, serum biochemistry, antioxidant capacity, intestinal morphology, and intestinal microbiota of broiler chickens - Hou, Jinwang; Lu, Lizhi; Lian, Lina; Tian, Yong; Zeng, Tao; Ma, Yanfen; Li, Sisi; Chen, Li; Xu, Wenwu; Gu, Tiantian; Li, Guoqin; Liu, Xin (Frontiers in Microbiology, 2024)
Introduction: This study examined the impact of adding coated sodium butyrate (CSB) to the diet on the growth performance, serum biochemistry, antioxidant capacity, intestinal morphology, and cecal microbiota of yellow-feathered broiler chickens. Methods: In this study, 240 yellow-feathered broiler chickens at 26 days old were divided into two groups: the control group (CON group) received a standard diet, and the experimental group (CSB group) received a diet with 0.5 g/kg of a supplement called CSB. Each group had 6 replicates, with 20 chickens in each replicate, and the experiment lasted for 36 days. Results: Compared to the CON group, the CSB group showed a slight but insignificant increase in average daily weight gain during the 26-62 day period, while feed intake significantly decreased. The CSB group exhibited significant increases in serum superoxide dismutase, catalase, and total antioxidant capacity. Additionally, the CSB group had significant increases in total protein and albumin content, as well as a significant decrease in blood ammonia levels. Compared to the CON group, the CSB group had significantly increased small intestine villus height and significantly decreased jejunal crypt depth. The abundance of Bacteroidetes and Bacteroides in the cecal microbiota of the CSB group was significantly higher than that of the CON group, while the abundance of Proteobacteria, Deferribacteres, and Epsilonbacteraeota was significantly lower than that of the CON group.